2015
DOI: 10.1111/wrr.12312
|View full text |Cite
|
Sign up to set email alerts
|

Compression‐induced HIF‐1 enhances thrombosis and PAI‐1 expression in mouse skin

Abstract: Pressure ulcers result from tissue hypoxia caused by external forces. Thrombosis due to external forces is considered important, and hypoxia inducible factor-1 (HIF-1) is a master regulator of pressure ulcer development. To date, however, their causal relationship has not been determined. This study therefore investigated the mutual relationship between thrombosis and HIF-1 activation in compressed mouse skin, based on a hypothesis that HIF-1 regulation by plasminogen activator inhibitor-1 (PAI-1) enhances thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Moreover, emerging evidence suggests that mechanical forces can trigger HIF-1 induction. For example, HIF-1α can be induced by mechanical stretching in capillary endothelial cells 48 , by compression in skin cells 49 , and by pressure in heart ventricles 50 . HIF-1α is also upregulated in the brain cortex following traumatic brain injury 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emerging evidence suggests that mechanical forces can trigger HIF-1 induction. For example, HIF-1α can be induced by mechanical stretching in capillary endothelial cells 48 , by compression in skin cells 49 , and by pressure in heart ventricles 50 . HIF-1α is also upregulated in the brain cortex following traumatic brain injury 51 .…”
Section: Discussionmentioning
confidence: 99%
“…A histopathological study in non‐blanchable erythema has shown abundant fibrin thromboses in the reticular dermis and subcutaneous tissue . Kaneko et al also reported that compression of mouse skin significantly increased the number of thromboses. Consistent with these findings, we found thromboses in the dermis in the I/R site in control mice.…”
Section: Discussionmentioning
confidence: 93%
“…Cutaneous I/R injury has been reported to induce thromboses and to suppress the luminal areas of blood vessels in the dermis, as well as to induce hypoxia and oxidative stress at the I/R site . Based on these previous studies, we investigated the effects of BBP on blood vessels in the I/R area in a cutaneous I/R injury model.…”
Section: Resultsmentioning
confidence: 99%
“…First, the study has employed a murine skin wound ischemia reperfusion model of pressure injury. Although this model has been validated in multiple publications, 1215,3739 the translatability of findings in a murine skin model to the human condition faces some challenges. Rodent skin healing occurs in part due to contraction rather than reepithelialization.…”
Section: Discussionmentioning
confidence: 99%